Lustration: The Definition and Legal Aspects - Stevanović, Aleksandar (Zbornik Instituta za kriminološka i sociološka istraživanja, 2018)
In this paper, the author speaks about the key legal aspects of lustration and its function in a democratic society. The aim of the article is to highlight lines of influence and consequences of the Lustration laws. Lustration should be regarded as an important mechanism of transitional justice, and an official process that addresses the suitability of former regime officials for public posts in a new democratic society. When it comes to the nature and classification of the lustration, it has to be mentioned that there are still many disagreements about that topic. We understand lustration as a non-criminal sanction for past behaviour considered negative by society. As we have noted, lustration is usually discussed as an aspect of the so-called ’retroactive justice’. Nevertheless we underlined the prevention aspect that could be regard as very significant lustartuion component.